PKM Kelompok Ternak Kambing Bali Farms Desa Kesiut Dalam Meningkatkan Nilai Tambah Usaha Melalui Rekayasa Pakan Kaya Nutrisi (Repakansi) - Komang Dean Ananda; I GD Yudha Partama; Dewa Gede Agung Gana Kumara (Jurnal Pengabdian UNDIKMA, 2022)
This service aims to increase the knowledge and value-added of the Bali Farms goat group business through nutrient-rich feed engineering (Repakansi). The service methods were Knowledge Transfer, Technology Transfer (TT), Science and Technology Diffusion, and Entrepreneurship Capacity Building approaches. This community service partner was the Bali Farms goat group, Kesiut Tabanan Village, Bali. The results of this service showed that the level of knowledge of the Bali farms goat group regarding nutrient-rich feed engineering (Repakansi) for goats was 45% at the pretest and 83% at the posttest, with a percentage increase of 92%. Thus, the mandatory output target is achieved, which was 90-100% of partners showing an increase in the percentage level of knowledge in making reparations.